Síntese e propriedades fotoluminescentes de complexos bis-dicetonatos de íons lantanídeos trivalentes com ligantes fosfinóxidos - Silva Jr, Francisco Andrade da (2011)
This work reports the synthesis, characterization, and investigation of the photoluminescent properties of β-diketonate complexes (TTA= 2-thenoyltrifluoroacetonate and DBM = dibenzoylmethanate) of trivalent lanthanides (Ln3+ = Eu3+, Tb3+ and Gd3+ ) with different phosphine oxides ligands (TPPO = triphenylphosphine oxide and HMPA= hexamethylphosphoramide). The elemental C, H, and N analyses, and complexometric titration suggested the general formulas [Ln(TTA)2(NO3)L2], [Ln(DBM)2(NO3)L2], [Ln(DBM)(NO3)2(HMPA)2], [Ln(TTA)3L2] e [Ln(DBM)3L], where L is phosphine oxide ligand. The absorption spectra in the infrared region showed that the coordination of β-diketonate and phosphine oxide ligands to Ln3+ ions occurs through the oxygen atoms of the carbonyl and P = O groups, respectively. Molar condutivity measurements show that the compounds behave as non-electrolytes in solution for the solvents methanol and acetone. The complex Tb(TTA)2(NO3)(TPPO)2 was obtained as single crystals and its structure was resolved by X-ray diffraction. The split transitions 5D0→7FJ, in general, are consistent with a chemical environment of low symmetry around the Ln3+ ion. The phosphorescence spectra of the Gd3+complexes showed the triplet state (T) bands of the ligands TTA and DBM, which were increased in energy (of the triplet state) in the bis- and mono-diketonate complexes in comparison with the tris-diketonates analogous. The tris-diketonate complexes of TTA and DBM showed a higher value of intensity parameters Ω2 when compared with their respective mono-and bis-diketonate, reflecting a chemical environment more polarizable around the ion Ln3+ to these complexes.